FROM THEORY TO PRACTICE: ENHANCING ENGLISH LANGUAGE COMPETENCIES IN THE INTEGRATED CLASSROOM - Abdukarimov Abdulvohid (TADQIQOTLAR, 2026)
This study explores the transition from theoretical frameworks of language learning to practical implementation in the integrated classroom, with a particular focus on enhancing English language competencies. In contemporary language education, the integration of skills, content, and communicative practices has become a central principle, reflecting the need for holistic and learner-centered approaches. The research examines how theoretical models such as communicative language teaching, task- based learning, and content and language integrated learning (CLIL) can be effectively operationalized in classroom settings to develop learners’ linguistic, communicative, and intercultural competencies. By applying pedagogical analysis, comparative evaluation, and classroom-oriented perspectives, the study identifies key strategies for bridging the gap between theory and practice. The findings suggest that integrated instruction not only improves language proficiency across the four skills listening, speaking, reading, and writing but also enhances critical thinking, collaboration, and learner autonomy. The paper highlights the importance of adaptive teaching methodologies, contextualized learning environments, and reflective practice in achieving effective language education outcomes.